ARANG AKTIF DARI SEKAM PADI SEBAGAI BAHAN PENYERAP LOGAM KROM DAN BESI DARI AIR LIMBAH PELAPISAN KROM - Taufik, Muhammad (KINETIKA, 2013)
Rice husk is the abundant agricultural waste in Indonesia, with increased production year to year that would be harming the environment. However, after research can be known that rice husk has the main content of Carbon and Silica , porous and amorphous structures. Of the nature of the rice husk, rice husk shows that have the ability to adsorb heavy metal ions. With its ability as an adsorbent material to be motivated to usage rice husk as adsorbent in the adsorption of chrome and iron from chrome plating waste water and is expected to reduce environmental pollution. The adsorption process is begun by clean up and drying under the sunshine, carbonized,size reduction and activated at activator concentration of 0,1M, 0,2M, 0,3M, 0,4M,and 0,5M.Then filter and drying in the oven.Â  Adsorption is then performed with the variation between the chrome plating wastewater with adsorbent for +20 mesh, -20+60 mesh, -60+170 mesh, -170+200 mesh, -200 mesh sizes with the activator concentration adsorbent. This study aims to determine the adsorption efficiency with variation of the size adsorbent and the activator concentration adsorbent used to secure the metal plating wastewater discharged into the environment. The results showed that the optimal adsorption of chrome and iron Â metals from chrome plating wastewater occurs at -170+200 mesh sizes and adsorbent concentration of 0,3M, with -60+170 mesh sizes and adsorbent concentration of 0,4M. From the results of this study found that the rice husk can be used to adsorb the metals chrome and iron from chrome plating wastewater.